Integration of Artificial Intelligence and Modern Medicine - Ergasheva Madina Khusniddin qizi; Abdujabborova Diyora Djalaliddin qizi (Genius Journals, 2026)
This academic article deeply analyzes the integration of artificial intelligence (AI) and modern medicine. It examines AI's main applications in diagnostics, drug discovery, and personalized medicine. The advantages of this integration for healthcare systems, such as increased efficiency, accuracy, and new opportunities, are thoroughly discussed. Concurrently, key challenges and limitations, including data management, ethical dilemmas, and regulatory constraints, are critically explored. Finally, the future prospects of AI in medicine, development trends, and recommendations for ensuring the safe, equitable, and effective integration of this transformative technology are presented
Keywords: Artificial intelligence; Medicine; Diagnostics